Simplifying
3m = 5(m + 3) + -3
Reorder the terms:
3m = 5(3 + m) + -3
3m = (3 * 5 + m * 5) + -3
3m = (15 + 5m) + -3
Reorder the terms:
3m = 15 + -3 + 5m
Combine like terms: 15 + -3 = 12
3m = 12 + 5m
Solving
3m = 12 + 5m
Solving for variable 'm'.
Move all terms containing m to the left, all other terms to the right.
Add '-5m' to each side of the equation.
3m + -5m = 12 + 5m + -5m
Combine like terms: 3m + -5m = -2m
-2m = 12 + 5m + -5m
Combine like terms: 5m + -5m = 0
-2m = 12 + 0
-2m = 12
Divide each side by '-2'.
m = -6
Simplifying
m = -6